MEASURING UMKM SALES PERFORMANCE THROUGH COMPETITIVE ADVANTAGE: IN THE CONTEXT OF DIGITALIZATION USE IN MEDAN CITY - Simanjuntak, Agus N.; Silaban, Frederick Saroha; Steven, Orlando; Simanjuntak, Sabriana S. (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2024)
The COVID-19 pandemic has had a major impact on many industries, including the economy. Indonesia's economic and business sectors have been hit hard by the Covid-19 outbreak. Many micro, small and medium enterprises (MSMEs) are confused because their companies are blocked and cannot even develop. Globally, supply chains have weakened due to the impact of Covid-19, commodity prices have plummeted, and the possibility of a global economic crisis is increasing. The widespread spread of the corona virus or Covid-19 is starting to impact more than half of the cooperatives and Small and Medium Enterprises in North Sumatra. There are around 2.8 million MSMEs in northern Sumatra, but no more than 20% of those who have permits or licenses at the Cooperative Office are around, 380,000. The position of MSMEs is considered very significant because this sector is not only a source of livelihood, but also provides direct and indirect employment opportunities to people with relatively low levels of knowledge and skills. The payment system industry developed the Quick Response Code Indonesia Standard (QRIS) together with Bank Indonesia (BI) to make processing transactions using QR codes easier, faster and more efficient. Based on the existing conditions, the aim of this research is to improve the digital payment system to improve the sales performance of MSMEs in the city of Medan. The aim of this research is to measure and examine the ability of the variables usage of e-commerce, usage of QRIS, digitalization transformation in increasing competitive advantage and ultimately increasing the sales performance of MSME players in the city of Medan. The research results conclude that usage of e-commerce, usage of qris, digital transformation positively and significantly predict competitive advantage. Apart from that, this research also confirms that digital transformation positively and significantly predicts sales performance.